1896. Statewide Genomic Surveillance of SARS-CoV-2 Variants in Rhode Island. (15th December 2022) - Singh, Manjot; Novitsky, Vladimir; Howison, Mark; Carpenter-Azevedo, Kristin; Huard, Richard; King, Ewa; Kantor, Rami
Abstract: Background: Global genomic surveillance has allowed identification of SARS-CoV-2 circulating variants responsible for the COVID-19 pandemic. Statewide variant characterization can guide local public health mitigations and provide educational opportunities. We characterized statewide evolution of SARS-CoV-2 variants in Rhode Island (RI). Methods: Deidentified RI SARS-CoV-2 sequences since 2/2020, generated at authors, CDC and commercial laboratories, were extracted from https://www.gisaid.org. Genomic and phylogenetic analyses were conducted with available tools and custom python scripts and, after quality control, sequences were classified as variants of Concern (VOC), variants being monitored (VBM), or non-VOC/non-VBM, per CDC definitions. Specific mutations that are characteristic of the most recent VOCs (Delta or Omicron) were explored outside of their designated lineages. Results: Of the 1.1 million RI population, 14, 933 SARS-CoV-2 sequences were available between 2/2020 and 3/2022. These included 1, 542 (11%) sequences from 37 non-VOC/non-VBM lineages until 2/2021, most commonly B.1.2 (21%), B.1.375 (13%), and B.1.517 (6%); 2, 910 (19%) sequences from 7 VBM lineages between 3-6/2021, most commonly Alpha (48%), Iota (34%), and Gamma (10%); and 10, 481 (70%) sequences from 2 VOC lineages, including 7, 574 (72%) Delta mostly between 6/2021 and 12/2021, and 2, 907 (28%) Omicron mostly between 1/2022 and 3/2022. Phylogeny showed expected clustering of local variants within regional and global sequences, and continued viral evolution over time. Further VOC evolution was observed, including 87 Delta sub-lineages, most commonly AY.103 (17%), AY.3 (15%), and AY.44 (12%); and 4 Omicron sub-lineages BA.1 (61%), BA.1.1 (32%), BA.2 (7%), and BA.3 (< 1%). Omicron-associated mutations S:del69/70, S:H655Y, or N:P13L were observed in 219 Delta sequences, and Delta-associated mutations ORF1b:G662S, N:D377Y, or M:I82T were observed in 16 Omicron sequences. Conclusion: Statewide SARS-CoV-2 genomic surveillance allows for continued characterization of locally circulating variants and monitoring of viral evolution. Such data guide public health policies, inform the local health force, and mitigate the impact of SARS-CoV-2 on public health. Disclosures: Rami Kantor, MD, Gilead Sciences: Grant/Research Support.